Synthesis and characterization of carbon nanotubes and nano alumina-reinforced aluminum matrix nanocomposites - Toozandehjani, Meysam (2017)
Owing to the unique properties of carbon nanotubes (CNTs) and alumina (Al₂O₃) nanoparticles, they have been incorporated into aluminum matrix as the reinforcement to fabricate light-weight Al-Al₂O₃ and Al-CNTs nanocomposites. Al-Al₂O₃ and Al- CNTs have been widely used in different applications in aerospace, automotive and military industries due to excellent combination of properties including high strength, high stiffness and good wear resistance as well as improved thermal and electrical properties. Addition of even small amount of these nanoparticles provides effective improvement of the overall physical and mechanical behaviour of nanocomposites. However, incorporating of CNTs and Al₂O₃ nanoparticles into aluminium matrix is difficult task particularly when larger contents of these nanoparticles are used. The aim of this research was to investigate the feasibility of synthesizing of Al-Al₂O₃ and Al-CNTs as well as hybrid Al-CNTs-Al₂O₃ nanocomposites by using a combination of mechanical ball milling and powder metallurgy route. The effect of hybridization of Al matrix by the addition of both CNTs and Al₂O₃ nanoparticles on morphology and microstructural features and subsequent effect on physical and mechanical behavior of hybridized nanocomposites was investigated and compared with single-reinforced Al-CNTs and Al-Al₂O₃ nanocomposites. Finally, the applicability of ultrasonic non-destructive evaluation technique for characterization of the microstructure and mechanical properties of all nanocomposites was studied. To achieve the proposed research objectives, all nanocomposites were synthesized using a combination of ball milling and powder metallurgy route. Ball milling at different times was employed to disperse different contents of CNTs and Al₂O₃ nanoparticles within aluminum powder. Nanocomposite powders were then consolidated by compaction at 150 MPa followed by sintering at 530 °C. Structural and microstructural features were characterized as a function of milling time and nanoparticles contents using SEM, FESEM, TEM, HRTEM, particle size analyzer, XRD and Raman spectroscopy. Physical and mechanical behavior of nanocomposites was characterized using density, hardness, compression and nanoindentation tests. Ultrasonic measurements were carried out to measure ultrasonic parameters; ultrasonic velocity and attenuation in order to establish a correlation between ultrasonic parameters and structural, microstructural and physical and mechanical properties of these nanocomposites. The results revealed that designated ball milling contributes to a homogenous dispersion of different amount of CNTs and Al2O3 nanoparticles, reduction of particle clustering, reduction of inter-particle spacing, reduction in particle size and grain refining. However, designated ball milling was found to be not efficient in dispersion of CNTs content more than 2 wt.% while it was efficient in dispersion of different amount of Al₂O₃ up to 10 wt.%. These morphological and microstructural variations within milling process significantly affect the physical and mechanical behaviour of Al-CNTs and Al-Al₂O₃ nanocomposites. Most interestingly, hybridization of Al-CNTs- Al₂O₃ nanocomposites exerts better physical and mechanical properties as compared to Al-CNTs and Al-Al2O3 nanocomposites. It was found that micro-hardness, nanohardness and Young‘s modulus of Al-2CNTs-Al₂O₃ nanocomposites significantly increases by increasing Al₂O₃ content by 35%, 30 % and 38%, respectively. Further, ultrasonic measurement revealed a good correlation between ultrasonic parameters with microstructural features and mechanical properties induced by ball milling and further powder metallurgy route.